Isolation and Identification of Non-Symbiotic Nitrogen-Fixing Bacteria in Prancak Village Tobacco Farming Soil - Hefdiyah, Hefdiyah; Rofiqoh, Rofiqoh (Universitas Brawijaya, 2025)
Prancak 95 is one of the most prominent tobacco (Nicotiana tabacum L.) varieties in Indonesia, originating from Prancak Village, Madura. Among the essential nutrients required for tobacco growth, nitrogen plays a crucial role in supporting vegetative and reproductive development. Although atmospheric nitrogen is abundant, constituting approximately 78% of the air, it is unavailable to plants in its diatomic form (N2). One sustainable approach to increasing nitrogen availability in soil is through the activity of non-symbiotic nitrogen-fixing bacteria (NFB), which convert atmospheric nitrogen into plant-accessible forms. This study aimed to isolate and identify non-symbiotic NFB from Prancak 95 tobacco farmland soils, in order to assess their population density, nitrogen-fixing potential, and taxonomic affiliation. Soil samples were collected from two locations in Prancak Village: West Tegal and Bilamabuk hamlets. Bacterial isolation was carried out using the pour plate method on Yeast Extract Mannitol Agar (YEMA) medium, followed by incubation at 37°C for 3 days. Pure bacterial isolates were subjected to macroscopic, microscopic, and biochemical characterisation based on Bergey's Manual of Determinative Bacteriology. Nitrogen-fixation potential was assessed by measuring the clear zone diameter on YEMA medium supplemented with Congo red, and the clear zone ratio was used as an indicator of nitrogenase activity. The results showed that the average non-symbiotic NFB population in West Tegal was 3.25 × 105 CFU.g-1, while in Bilamabuk it was 2.7 × 105 CFU.g-1. A total of six bacterial isolates were selected for further study. All isolates demonstrated nitrogen-fixing potential, with clear zone ratios ranging from 1.26 to 2.60 cm. Based on morphological, microscopic, and biochemical analyses, isolates coded PT2, PB1, and PB3 were identified as belonging to the genus Bacillus, while isolates PT1, PT3, and PB2 were tentatively identified as members of the genus Corynebacterium.